Measuring Community Benefits Provided by Nonprofit and For-Profit HMOs - Mark Schlesinger; Shannon Mitchell; Bradford Gray (SAGE Publishing, 2003)
Despite the dramatic shift from nonprofit to for-profit ownership in the managed care industry, little is known about the implications for health plans' relations with the communities in which they operate. This paper provides the first comprehensive comparison of the community benefit activities of nonprofit and for-profit health maintenance organizations (HMOs). We develop a conceptual framework for identifying these activities and provide evidence from a nationally representative survey of plans fielded in 1999. We find that nonprofit plans exceed their for-profit counterparts on some, but not all, aspects of community benefit activity. The most consistent ownership-related differences involve redistributive programs (subsidized services and general philanthropy), commitments to medical research, and services that benefit the entire local population, beyond the plan's enrollees. Other forms of community benefits show mixed or modest differences between nonprofit and for-profit plans. Unexpectedly, for-profit plans actually appear more active in helping consumers deal with information asymmetries. The paper concludes with a discussion of implications for policy and future research.